BSA-Silver Nanoparticles: A Potential Multimodal Therapeutics for Conventional and Photothermal Treatment of Skin Cancer - Dasom Kim; Reeju Amatya; Seungmi Hwang; Sumi Lee; Kyoung Ah Min; Meong Cheol Shin (MDPI AG, 2021)
Silver nanoparticles (NPs) have attracted a considerable interest in the field of cancer research due to their potential utility in cancer therapy. In the present study, we developed bovine serum albumin (BSA)-coated silver NPs (BSA-Silver NPs) and characterized in vitro multimodal therapeutic activities of NPs for the treatment of skin cancer. BSA-Silver NPs were synthesized by a single-step reduction process, and the successful preparation was verified through a list of physical characterizations, including transmission electron microscopy (TEM), ultraviolet-visible (UV-VIS) light spectroscopy, dynamic light scattering (DLS), and Fourier transform infrared (FT-IR) spectroscopy. The synthesized BSA-Silver NPs showed marked cytocidal effects on B16F10 melanoma cells, which was likely caused by oxidative stress. BSA-Silver NPs also elicited significant anti-angiogenic effects on HUVEC (human umbilical vein endothelial cell) by inhibiting their proliferation, migration, and tube formation. Moreover, BSA-Silver NPs showed a considerable light-to-heat conversion ability, suggesting their utility as photothermal agents. Overall, our findings suggest that BSA-Silver NPs may be promising candidates for the multimodal therapy of skin cancer.